Unblocking temperature of secondary magnetic component to outline anomaly thermomagnetic maps of archaeological fireplaces from the southern region of Mexico City, Mexico - Arnaldo Hernández-Cardona; Luis Manuel Alva-Valdivia; Guillermo Acosta-Ochoa; Amar Agarwal; Tamara Cruz-y-Cruz; Emily McClung de Tapia (Revista Mexicana de Ciencias Geológicas)
We report a magnetic study of two preceramic hearths located at the southern region of Mexico City. Thermal demagnetization was applied between 200 to 540 °C to define the remanent magnetization components. The maximum unblocking temperature of the secondary magnetic component reached due to the last heating was identified in most samples. They were used to develop thermomagnetic anomaly source maps. The direction of this component was used to place the blocks to their last cooling spot and configurate a real and primal magnetic anomaly map produced by the thermoremanent magnetization acquired. A protocol to relocate blocks frame is proposed using geomagnetic secular variation curves. The thermomagnetic mapping revealed the position and temperature (220 to 460 °C) of the last heat sources. The distribution of these sources allowed to model an extensional zone of benefit and probable uses of the hearths.